Hubungan Kekuatan Otot Tungkai dan Koordinasi Mata-Kaki dengan Kemampuan Passing Sepakbola Menggunakan Kaki Bagian Dalam pada Siswa SMA Mutiara Bangsa - Rusdi Gobel; Rifaid Saiman (Indonesian Journal of Physical Activity, 2022)
To perform good passing, strong leg muscles and good coordination are necessary. The purpose of this research is to determine the leg muscle strength, eye-foot coordination, and the ability to perform inside foot passing in soccer among high school students at Mutiara Bangsa. This research uses a correlational quantitative method with a sample of 30 students, using the simple random sampling technique. The research results show: (1) There is a relationship between leg muscle strength and the ability to perform inside foot passing in soccer among high school students at Mutiara Bangsa, with an r-value of 0.897 > r-table value of 0.361. (2) There is a relationship between eye-foot coordination and the ability to perform inside foot passing in soccer among high school students at Mutiara Bangsa, with an r-value of 0.801 > r-table value of 0.361. (3) There is a simultaneous relationship between leg muscle strength and eye-foot coordination with the ability to perform inside foot passing in soccer among high school students at Mutiara Bangsa, with an F calculated value (57.583) > F-table value (3.35).